Modeling the demand for factors of production in the mechanical engineering industry of Northern Ireland, 1954-79 - Harris, R (Economic & Social Studies, 1988)
This paper estimates an econometric model of the demand for the factors of production using data available for the Mechanical Engineering industry in Northern Ireland. The primary aim is to demonstrate that it is possible to use Northern Ireland data and obtain meaningful results, and this should encourage a more extensive coverage of industries in the North in the near future. Section II looks at different dynamic factor demand models and sets out the basic model that is estimated, while Section III discusses the data that are required. Section IV presents the method of estimating the model, the results obtained, and tests of the model's specification. Finally, the paper ends with a summary and conclusion.
Keywords: Mechanical engineering - Northern Ireland - Economic aspects; Industry - Northern Ireland - Economic aspects